Synthesis of cellulase in the cultures of bacteria Paenibacillus sp. isolated from the rhizosphere - Dobrzyński, Jakub; Sitarek, Monika; Słodownik, Patrycja; Jankiewicz, Urszula; Gozdowski, Dariusz; Górska, Ewa B. (Studia Ecologiae et Bioethicae, 2017)
From the rhizosphere soil of apple, cherry, and strawberry fertilized with composts on the basis of brown coal fine with the addition of mycelium from Basidiomycota, 6 strains of facultatively anaerobic, spore-forming and able to degrade cellulose bacteria were isolated. On the basis of morphology and 16S rRNA sequences, the isolates were classified into Paenibacillus sp. In the selective media supplemented with filter paper (FP) and carboxymethylcellulose (CMC) strains, which synthesize cellulolytic enzymes responsible for the hydrolysis of amorphous and crystalline cellulose were tested. After 14 and 28 days culture in the medium with CMC tested isolates produced similar amounts of carboxymethylcellulase (CMCase) respectively 0 – 10,87 mU and 10,73 – 21,13 mU. The highest synthesis of the enzyme, which saccharifying cellulose (FPase) was found in the 14-day culture of P. lautus EG_11 – 75,6 mU, Paenibacillus sp. EG_17 – 57,6 mU and P. woosongensis EG_15 – 38,9 mU. In the medium supplemented with FP, the highest synthesis of the CMCase and FPase reported in cultures of P. lautus EG_11, it was respectively 79,85 and 118,83 mU.